Lean ergonomics: A three-dimensional analysis of progress, practical challenges, and prospective research - Nofirza, Nofirza; Hadiguna, Rika Ampuh; Amrina, Elita (Journal Industrial Servicess, 2024)
Lean systems and ergonomics are two organizational approaches that were initially practiced independently. Over time, however, it has become evident that while lean methodology emphasizes efficiency and waste reduction, it often overlooks the human factor, which can compromise worker health and safety. On the other hand, applying ergonomics without incorporating lean principles may lead to inefficiencies and increased costs. This trade-off has sparked growing interest in integrating ergonomic considerations into lean practices within manufacturing. Despite this interest, comprehensive studies on lean ergonomics remain scarce. This research aims to explore the development of lean ergonomics implementation over the past five years. Using a Systematic Literature Review (SLR) methodology, the study analyzed articles from two Scopus-indexed databases, identifying 196 articles containing the keywords Lean, Ergonomics, and Manufacturing Industries. Following the PRISMA framework and applying inclusion criteria, only 18 papers were found to thoroughly address the integrated implementation of lean ergonomics in manufacturing industries. The majority of these studies originated from Portugal (33.33%) and India (16.67%). Case studies emerged as the dominant research methodology (55.56%), leading to the development of lean ergonomic tools such as Ergo-VSM, ErgoSMED, and WIDEA. Other methodologies included literature reviews (22.22%), qualitative research (16.67%), and grounded theory (5.56%). The findings suggest that implementing lean ergonomics has positive impacts, including reduced setup times, decreased ergonomic risks, and improved workplace conditions. While ergonomic interventions may involve additional costs, these are viewed as long-term investments. In conclusion, the existing literature indicates that the implementation of lean ergonomics is still limited and lacks comprehensiveness. Future research could focus on practical applications in industry and evaluate their effectiveness to strike a balance between operational efficiency and worker well-being.